2016
DOI: 10.1371/journal.pone.0145943
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Incidence Rates of Diarrheal Disease Associated with Norovirus, Sapovirus, and Astrovirus in Kenya

Abstract: BackgroundDiarrheal diseases remain a major cause of mortality in Africa and worldwide. While the burden of rotavirus is well described, population-based rates of disease caused by norovirus, sapovirus, and astrovirus are lacking, particularly in developing countries.MethodsData on diarrhea cases were collected through a population-based surveillance platform including healthcare encounters and household visits in Kenya. We analyzed data from June 2007 to October 2008 in Lwak, a rural site in western Kenya, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
8
21
1
Order By: Relevance
“…After RV, NoV was the second most predominant virus. A similar observation was made by other groups from India and worldwide, 6,22,[31][32][33][34] but at the same time lower prevalence was seen in UK 35 and Australia. 36 NoV genogroup GII showed higher incidence as compared to GI genogroup in both study periods which is in accordance with previous reports from India and other countries.…”
Section: Discussionsupporting
confidence: 87%
“…After RV, NoV was the second most predominant virus. A similar observation was made by other groups from India and worldwide, 6,22,[31][32][33][34] but at the same time lower prevalence was seen in UK 35 and Australia. 36 NoV genogroup GII showed higher incidence as compared to GI genogroup in both study periods which is in accordance with previous reports from India and other countries.…”
Section: Discussionsupporting
confidence: 87%
“…Due to the small number of urban sewage samples, it was difficult to detect outbreaks as no prior information concerning baseline pathogen abundance values exist from these sites. As viral tests were not routinely performed on stools collected through PBIDS surveillance during this study period, the presence of viruses among diarrhea cases could not be confirmed, although the metagenomic findings were in line with previous studies [34]. The PBIDS surveillance datasets were limited in the number of reported illnesses, diarrhea, AFI, subjective fever and clinic visits at the household level, making direct comparison between population-based disease surveillance and the relative abundances observed in metagenomics sewage surveillance very difficult and challenging.…”
Section: Discussionsupporting
confidence: 62%
“…Interestingly, the PBIDS data did not show a peak in diarrheal cases during a time with significantly high read abundances for astrovirus 1, norovirus and sapovirus observed in both surveillance clusters in weeks 26 and 27. These viruses have recently been shown to be major contributors to gastroenteritis in Kibera, both alone and as coinfections [34]. Astrovirus MLB3 was another viral pathogen observed that temporally increase and is suspected to cause gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated number of 6.3 million deaths of children under the age of 5 years suffering from diarrhoea have been reported worldwide [ 1 , 2 ]. In Africa, death due to diarrhoeal disease remains a major health concern, though it has decreased from 2.6 million to 1.3 million between 1990 and 2013 [ 3 ]. Diarrhoeal disease is the important cause of morbidity and mortality in low and middle income countries, also the third most frequent cause of death and greatest contributor to the burden of disease in children younger than 5 years of age [ 4 ].…”
Section: Introductionmentioning
confidence: 99%